Impact of climate and management on coffee berry disease and yield in coffee's native range - Ayalew, Biruk; Hylander, Kristoffer; Adugna, Girma; Zewdie, Beyene; Zignol, Francesco; Tack, Ayco J.M. (Basic and applied ecology, 2024)
Climate change might increase plant diseases, reduce crop yields and threaten the livelihoods of millions of smallholder farmers globally. It is thus important to understand the relationships between climate, disease levels and yield to improve management strategies for sustainable agroforestry in a changing climate. One of the major threats to coffee production in Africa is the coffee berry disease (Colletotrichum kahawae). To investigate the effects of climatic and management variables on coffee berry disease (CBD) incidence and yield, we recorded minimum and maximum temperature and relative humidity, as well as CBD and yield, along a broad environmental and management gradient in southwestern Ethiopia during two consecutive years. CBD was affected by several climatic and management variables. For example, CBD incidence increased with minimum temperature during the fruit expansion stage, and decreased with minimum temperature during the endosperm filling stage. CBD incidence was negatively affected by the proportion of resistant cultivars, whereas the coffee structure index (pruning) had no effect on disease incidence. Coffee yield decreased with increasing minimum temperature during the flowering period in 2018 and maximum temperature during the fruit developmental period in 2019. Coffee yield was negatively affected by canopy cover and positively affected by the coffee structure index in both years. Our findings highlight that CBD and yield were affected by different climatic and management variables. Yet, managing for low disease levels and high yield is practically difficult due to season-dependent effects of several climatic variables. One way to break the correlation of climatic variables between seasons might be to take advantage of differences among shade trees in the presence or timing of leaf drop. To reduce CBD incidence, using resistant cultivars is an effective strategy, but this might threaten the wild coffee genetic reservoir.